2018
DOI: 10.1016/j.seizure.2018.08.008
|View full text |Cite
|
Sign up to set email alerts
|

Does emergent implantation of a vagal nerve stimulator stop refractory status epilepticus in children?

Abstract: VNS can be effective in treating refractory or super-refractory Status Epilepticus.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 11 publications
(16 citation statements)
references
References 19 publications
0
12
0
1
Order By: Relevance
“…Vagus nerve stimulation (VNS) may serve as an alternative or adjunct therapy for dogs with refractory epilepsy. This method has been utilized in human medicine for treatment of various diseases, including pharmacoresistent epilepsy and status epilepticus (7,8). Side effects attributed to the implantable device in humans are minimal, most often causing a voice change and coughing, (7) although there have been more severe documented complications related to the surgical procedure used to implant the device.…”
Section: Introductionmentioning
confidence: 99%
“…Vagus nerve stimulation (VNS) may serve as an alternative or adjunct therapy for dogs with refractory epilepsy. This method has been utilized in human medicine for treatment of various diseases, including pharmacoresistent epilepsy and status epilepticus (7,8). Side effects attributed to the implantable device in humans are minimal, most often causing a voice change and coughing, (7) although there have been more severe documented complications related to the surgical procedure used to implant the device.…”
Section: Introductionmentioning
confidence: 99%
“…A systematic review showed VNS implantation was associated with cessation of 74% (28/38) RSE/SRSE patients in acute phase [7]. A case report presented three out of four genetic SE cases with success cessation by VNS implantation, which seemed even more tough than non-genetic SE [8], and gave us more evidence of applying VNS in our patient though no FIRES case has been reported with VNS successful management.…”
Section: Discussionmentioning
confidence: 66%
“…Four cases have recently been reported with patients presenting different conditions: hemimegaloencephaly, non-ketotic hyperglycinemia, migrating focal seizures of infancy, and microdeletion of 1q43q44 causing microcephalia, corpus callosum agenesia, and epilepsy. All four conditions were genetically determined, and the authors reported cessation of SE in three out of the four cases (14).…”
Section: Discussionmentioning
confidence: 98%